Morphology of Tantalum Nitride Thin Films Grown on Fused Quartz by Reactive High Power Impulse Magnetron Sputtering (HiPIMS). Issue 1803 (25th May 2015) - Thorsteinsson, D. O.; Tryggvason, T. K.; Gudmundsson, J. T.
ABSTRACT: Thin tantalum nitride films were grown on fused quartz by reactive high power impulse magnetron sputtering (HiPIMS) while varying the fractional N2 flow rate at fixed substrate temperature of 400°C. The film properties were compared to films grown by conventional dc magnetron sputtering (dcMS) at similar conditions. Structural characterization was carried out using X-ray diffraction and reflection methods. The HiPIMS process produces slightly less dense films than does dcMS and the surface roughness is similar for both the HiPIMS and dcMS grown films. The deposition rate for HiPIMS is up to 80 % lower than for dcMS but it can be roughly doubled by lowering the magnetic field strength by 30 %.